2006
DOI: 10.1002/pmic.200500517
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of in vitro protein–protein interaction techniques: Assessing contaminating background proteins

Abstract: Determination of protein-protein interactions is an important component in assigning function and discerning the biological relevance of proteins within a broader cellular context. In vitro protein-protein interaction methodologies, including affinity chromatography, coimmunoprecipitation, and newer approaches such as protein chip arrays, hold much promise in the detection of protein interactions, particularly in well-characterized organisms with sequenced genomes. However, each of these approaches attracts ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 46 publications
0
43
0
Order By: Relevance
“…Mass spectrometry (MS) analysis of the target protein elution fractions revealed that the following E. coli host proteins also coeluted in significant amounts: DnaK, GlmS, AceE, EF-Tu, ArnA, RnaseE, AtpF, the Rho transcription terminator, CRP, and SlyD (data not shown). Several independent studies, performed using different conditions or different E. coli strains, also reported many of the same contaminants after Ni ϩ2 affinity chromatography (5,13,18). The most common E. coli proteins listed in these previous reports were CRP, Fur, ArgE, DnaK, SlyD, GlmS, GlgA, ODO1, ODO2, Can (YadF), ArnA (YfbG), AceE, GroES, and GroEL.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mass spectrometry (MS) analysis of the target protein elution fractions revealed that the following E. coli host proteins also coeluted in significant amounts: DnaK, GlmS, AceE, EF-Tu, ArnA, RnaseE, AtpF, the Rho transcription terminator, CRP, and SlyD (data not shown). Several independent studies, performed using different conditions or different E. coli strains, also reported many of the same contaminants after Ni ϩ2 affinity chromatography (5,13,18). The most common E. coli proteins listed in these previous reports were CRP, Fur, ArgE, DnaK, SlyD, GlmS, GlgA, ODO1, ODO2, Can (YadF), ArnA (YfbG), AceE, GroES, and GroEL.…”
Section: Resultsmentioning
confidence: 99%
“…Protein samples of approximately 1 mg were added to 20 l of trypsin reaction buffer (50 mM Tris-HCl, 20 mM CaCl 2 , pH 8) and digested overnight at 37°C with trypsin (New England BioLabs) at a protein-to-protease ratio of 20:1. Online liquid chromatography coupled with tandem mass spectrometry (LC-MS-MS) analyses of digested fractions using an Agilent 6330 Ion Trap mass spectrometer with an integrated C 18 chromatin immunoprecipitation-nanoelectrospray ionization (C 18 ChIP/nano-ESI) interface were performed as described previously (40). Protein separation, digestion, and peptide analysis were repeated in triplicate for each sample.…”
Section: Sds-page and Western Blot Analysismentioning
confidence: 99%
“…In regard to the present findings with secondary hypoxia, Bramlett et al (1999b) reported that this complicated TBI model leads to a larger cortical contusion and aggravated hippocampal damage associated with a more robust inflammatory response. In previous studies, structural damage and an aggravated inflammatory response has been correlated with elevated IL-6 levels after brain injury (Howell et al, 2006;Yan et al, 2012). After stroke, for example, elevated levels of IL-6 are associated with the infarct size and poor outcome (Vila et al, 2000;Smith et al, 2004;Waje-Andreassen et al, 2005).…”
mentioning
confidence: 99%
“…After stroke, for example, elevated levels of IL-6 are associated with the infarct size and poor outcome (Vila et al, 2000;Smith et al, 2004;Waje-Andreassen et al, 2005). In this regard, IL-6 levels are considered a highly specific biomarker of TBI severity and long-term outcome (van Griensven et al, 2003;Howell et al, 2006). In addition, IL-6 plays an important role in activating and recruiting immune cells and has been reported to suppress TNF-a and IL-1-b production and stimulate nerve growth factor (NGF) production (Kushima et al, 1992;Juttler al., 2002).…”
mentioning
confidence: 99%
“…S6). Although a number of novel SHPS-1/CD binding partners were identified in the present study using the mRNA display and TAP tag method and the interactions were confirmed with co-immunoprecipitation, previous studies have shown that the evaluation of in vitro protein-protein interactions by multiple orthogonal techniques is essential (49). Thus, these interactions need to be validated using other orthogonal technique.…”
Section: Shps-1/cd Is Required For Igf-i-dependent Protein Synthesis-mentioning
confidence: 99%